Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/jof6020042
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Aspergillus fumigatus to Atorvastatin Leads to Altered Membrane Permeability and Induction of an Oxidative Stress Response

Abstract: Aspergillus fumigatus is a serious cause of disease in immune-deficient patients and in those with pulmonary malfunction (e.g., cystic fibrosis (CF), asthma). Atorvastatin is a member of the statin drug family, which are the main therapeutic agents used to decrease high serum cholesterol levels by inhibiting (HMG-CoA) reductase enzyme. The aim of the work presented here was to analyse the antifungal activity of atorvastatin and assess its effect on the virulence of A. fumigatus. Atorvastatin demonstrated stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“… Chin et al ( 1997 ); Ribeiro et al ( 2017 ) Saccharomyces cerevisiae 40 - CTZ, ITR, MIA - Cabral et al ( 2013 ) C. stellatoidea 16 - - - Esfahani et al ( 2019 ) Rhizopus oryzae 32 - ITR, KET - Nyilasi et al ( 2010 ) Paecilomyces variotii 32 - - - Nyilasi et al ( 2010 ) Aspergillus flavus > 128 - ITR - Nyilasi et al ( 2010 ) A. fumigatus 64 - ITR, FLC, MIA, KET (I) Stimulates oxidative stress response; (II) Inhibits ergosterol synthesis. Nyilasi et al ( 2010 ; Ajdidi et al ( 2020 ) Fluvastatin C. albicans 25 No effects in mice FLC - Nyilasi et al ( 2010 ); Lima et al ( 2019 ) C. glabrata 32–64 - - - Nyilasi et al ( ...…”
Section: Statinsmentioning
confidence: 99%
“… Chin et al ( 1997 ); Ribeiro et al ( 2017 ) Saccharomyces cerevisiae 40 - CTZ, ITR, MIA - Cabral et al ( 2013 ) C. stellatoidea 16 - - - Esfahani et al ( 2019 ) Rhizopus oryzae 32 - ITR, KET - Nyilasi et al ( 2010 ) Paecilomyces variotii 32 - - - Nyilasi et al ( 2010 ) Aspergillus flavus > 128 - ITR - Nyilasi et al ( 2010 ) A. fumigatus 64 - ITR, FLC, MIA, KET (I) Stimulates oxidative stress response; (II) Inhibits ergosterol synthesis. Nyilasi et al ( 2010 ; Ajdidi et al ( 2020 ) Fluvastatin C. albicans 25 No effects in mice FLC - Nyilasi et al ( 2010 ); Lima et al ( 2019 ) C. glabrata 32–64 - - - Nyilasi et al ( ...…”
Section: Statinsmentioning
confidence: 99%
“…The antifungal activity upholds by microdilution and diffusion methods ( Mahmoud et al, 2021 ). Furthermore, Ajdidi et al reported a reduction in aspergillus growth by atorvastatin-inhibiting effect and remarked elevation in membrane permeability proved by the detection of the augmented release of cell proteins ( Ajdidi et al, 2020 ). The observed antifungal activity in the blank-EMLs foam system was explained by SDS-fungal growth inhibition noticed by Woertz and Kinney ( Woertz and Kinney, 2004 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cabral et al discussed the antifungal mechanism and refer it to the ability of statins to suppress the fungal reductase enzyme (HMG-CoA) leading to declining in the ergosterol level followed by fungal growth suppression ( Cabral et al, 2013 ). Atorvastatin (ATO) is one of the statins reported with antimycotic activity on different fungus strains relying on previous microbiology studies ( Ajdidi et al, 2020 ; Mahmoud et al, 2021 ) Furthermore, previous work upholds the atorvastatin activity in animal models by formulating an emulgel to treat oral and vulvovaginal candidiasis ( de Oliveira Neto et al, 2021 ). Using ATO with this new therapeutic field as an antifungal agent can overcome the drug resistance issue of conventional drugs.…”
Section: Introductionmentioning
confidence: 99%
“…N-chlorotaurine inhibits conidial and mycelial growth in A. fumigatus by up-regulating the oxidative stress response ( Sheehan et al., 2019 ). Atorvastatin has treatment potential because it induces oxidative stress and alters membrane permeabilit y in A. fumigatus ( Ajdidi et al., 2020 ). Such novel antifungal drugs are welcomed additions in clinical therapy.…”
Section: Drug Action and Pharmacological Effects On Proteomic Profilesmentioning
confidence: 99%